Anatomical Points of Cupping Therapy for Musculoskeletal Pain: A Systematic Review - Aris Setyawan; Isma Nur Hikmah; Eka Oktavianto; I Made Moh. Yanuar Saifudin (Department of Nursing, Faculty of Medicine, Diponegoro University, 2022)
Background: The prevalence of musculoskeletal pain is rising and plays a substantial role in disease and disability worldwide. There have been several previous studies on cupping therapy’s effectiveness in reducing musculoskeletal pain. However, studies that specifically review the literature on cupping points to reduce musculoskeletal pain are lacking.Purpose: This study aimed to identify the anatomical points of cupping therapy for musculoskeletal pain.Methods: A systematic review was employed. PubMed, ScienceDirect, and Google Scholar were used for the search process. The screening was performed based on inclusion and exclusion criteria. Crowe Critical Appraisal Tool (CCAT) was used to measure the quality of the articles. Standardized forms were used to extract essential characteristics from articles, including study design, participant and sample, and results. Data were narratively analyzed for thematic synthesis.Results: From a total of 1,045 articles acquired, eight articles were included in data synthesis. All articles were randomized control trials (RCT) design. Seven regions of cupping points were identified, including upper-middle-lower fibres of the trapezius muscles, the inter-scapular area around the 2-4th vertebrae torachalis, the sacrum area, between the lower vertebrae and the coccyx bone, the 1-5th vertebrae lumbalis, the 3-5th vertebrae lumbalis, knee joint, and lower border of the spinous process of the second lumbar vertebra (L2).Conclusion: Seven anatomical points of cupping therapy for musculoskeletal pain were identified by this systematic review based on studies. Single research could not define the whole range of advantages of each point. To support the previously described theories regarding cupping and develop new ones, future novel scientific studies are also required.